Census of Population and Housing (United States), 1960 Public Use Sample: Modified 1/1000 State Samples ([Verlag nicht ermittelbar], 1984)
This collection consists of modified records from CENSUS OF POPULATION AND HOUSING, 1960 PUBLIC USE SAMPLE [UNITED STATES]: ONE-IN-ONE HUNDRED SAMPE (ICPSR 7756). The original records consisted of 120-character household records and 120-character person records, whereas the new modified records are rectangular (each person record is combined with the corresponding household record) with a length of 188, after the deletion of some items. Additional information was added to the data records including typical educational requirement for current occupation, occupational prestige score, and group identification code. This version differs from the original public-use sample in the following ways: ages of persons 15-74 are included, 10 percent of the Black population from each file is included, and Mexican Americans (identified by a Spanish surname) from outside Arizona, California, Colorado, New Mexico, and Texas are not included. This dataset uses the 1970 equivalent occupational codes. The Census Bureau originally used two separate codes for the 1970 and 1960 files, but these have been modified and are now identical.